The Elusive Concept of Class - Borgia Holteng, Adalgisa Diana (My University, 2024)
The concept of class has always been central in sociological theory and has generated endless debate. The aim of this dissertation is to explore an issue that I maintain has not received sufficient attention in sociological literature, namely, the competing understandings of class that underpin these debates. In this dissertation I conduct an in-depth analysis of four prominent theorists of class to show that class has been conceptualized in different and often contradictory ways. I focus on four key traditions: classical Marxism, Althusser's structuralism, Laclau's postmodernism, and Bourdieu's constructive or generic structuralism. I raise the question of whether the competing understandings of class in these theoretical traditions indicate a move towards abandoning the notion of class formations in sociological theorizing or whether they signify a movement towards a more complex, sophisticated, and encompasing understanding of class. After a deep-dive into understandings of class in the four traditions I have identified, I conclude by arguing that the latter is the case. That is, I argue that the shifts in the understandings of class represented in the work of Karl Marx, Louis Althusser, Ernesto Laclau and Pierre Bourdieu unveil a path towards a notion of class that can usefully guide and provide much needed coherence to the future discussions of class in sociology.
Keywords: concept of class